Upaya Pencegahan Polarisasi Politik di Tahun Pemilu 2024 - Rianadiwa, Syifa; Solakhudin, Faiz; Salam, Virgano Triadi; Rahmawati, Nurlaili (Sapientia Humana: Jurnal Sosial Humaniora, 2024)
This article aims to discuss efforts to prevent political polarization in the 2024 election year by using library data collection methods. The results of this research are that political polarization can occur in any situation and condition especially during elections, public policy, socio-cultural issues including post-debate issues for the Presidential and Vice Presidential Candidates. The causes of political polarization are none other than political parties, mass media, regional expansion, political context and society's political ideology. Political polarization has positive and negative impacts. However, of these two impacts, there are more negative impacts. The negative impacts that can be caused by political polarization are the creation of divisions, damage to democratic institutions, loss of credibility of political parties, impact on government, and reduced credibility of society, while the positive impacts of political polarization are strengthening relationships and increasing participation in politics. Political polarization will very easily occur when the public or supporters are easily carried away by issues circulating in society such as differences in ideology, choices and principles between one camp and another. Several efforts can be made to prevent political polarization, namely: the public must be able to sort and choose the issues circulating and not be too fanatical about their choices, instill and implement the values of Pancasila, and implement the value of harmonization of Bhinneka Tunggal Ika.